2011
DOI: 10.1590/s0037-86822011000100019
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação dos critérios diagnósticos do lúpus eritematoso sistêmico em pacientes com hanseníase multibacilar

Abstract: Diseases in our setting, such as leprosy in multibacillary forms, mimic the clinical and laboratory characteristics of SLE, and thus physicians need to be aware of the realities of local infectious diseases before affirming a definitive diagnosis of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Thus, physicians should consider leprosy in the differential diagnosis of SLE and/or antiphospholipid syndrome (APS) with unusual presentations, especially in endemic areas for leprosy, and order targeted biopsies. Patients can have malar rash, arthritis, photosensitivity, as well as the autoantibodies that can occur in lupus patients [23]. Joint involvement, mimicking rheumatoid arthritis, can also occur in leprosy.…”
Section: Discussion—rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, physicians should consider leprosy in the differential diagnosis of SLE and/or antiphospholipid syndrome (APS) with unusual presentations, especially in endemic areas for leprosy, and order targeted biopsies. Patients can have malar rash, arthritis, photosensitivity, as well as the autoantibodies that can occur in lupus patients [23]. Joint involvement, mimicking rheumatoid arthritis, can also occur in leprosy.…”
Section: Discussion—rheumatologymentioning
confidence: 99%
“…A variety of autoantibodies can be detected in leprosy patients such as double-stranded DNA (anti-dsDNA), anti-mitochondrial antibodies (AMA), and aPL [11, 12]. American College of Rheumatology (ACR) lupus classification criteria, which shows sensitivity and specificity of 96 and 84%, respectively, has 16% false-positive rate for lupus among Brazilian leprosy patients [23].…”
Section: Discussion—rheumatologymentioning
confidence: 99%
“…Critérios para Lúpus Eritematoso Sistêmico (LES), como artrite, rash malar, FAN, anticorpo antifosfolípides e linfopenia, segundo Teixeira Junior GJA e colspodem ter especificidade mais baixa em regiões com alta endemicidade para hanseníase 9 . Consideramos a baixa titulagem do FAN apresentada pela paciente (1:160), na ausência de outros critérios diagnósticos para LES fazendo corpo dessa afirmação.…”
Section: Discussionunclassified
“…Although its clinical presentation may be similar to that of chronic cutaneous lupus erythematosus, certain features of leprosy should alert the physician, such as anesthetic skin lesions, nerve enlargement, and nerve tenderness. Lesions may affect cutaneous peripheral nerves, primarily the posterior tibial nerve, ulnar, median, and lateral popliteal ( 24 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The specificity found (84%) was lower than the specificity allocated to the criteria in 1997 by the ACR. The authors concluded that leprosy in multi-bacillary forms mimics the clinical and laboratory characteristics of SLE, and thus physicians need to be aware of the realities of local infectious diseases before affirming a definitive diagnosis of SLE ( 24 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%